Legionella bozemanii serogroup 2: a new etiological agent. - Tang, P W (1984)
A newly discovered bacterium, Toronto 3, isolated from a lung aspirate of a patient with pneumonia, has been characterized. The isolate was identified as Legionella bozemanii by chemical data from cellular fatty acid and ubiquinone analyses and by DNA relatedness studies. The isolate, however, differs phenotypically from L. bozemanii by its colonial characteristics and strong interspecies serological cross-reactions, which are unique among clinical isolates of legionellae. The name L. bozemanni serogroup 2 is proposed. The reference strain is Toronto 3. The clinical illness caused by L. bozemanii serogroup 2 was not distinguishable from other Legionella infections. L. bozemanii is the third Legionella species with more than one serogroup. Rapid laboratory diagnosis of this strain by direct fluorescent antibody test may be complicated in the absence of culture isolation.